Analysis of Thin Film Fire Sensors. (1984) - Zentai, G.; Illyefalvi-Vitéz, Zs.
Abstract : The detection of fire in mines, industrial buildings, ships etc. is an important problem from both the economical and life-protecting aspects. The fire could be detected in several ways, e.g. by the measurement of flame-radiation, heat, pressure, temperature, the aerosols, the gases etc. The Department of Electronic Technology has developed a fire sensor which detects the rate of the increase of temperature. The fire sensor consists of two temperature sensitive resistors with different time-constants. If the increase of temperature in consequence of the fire is fast, the difference between the resistance of the temperature sensors is high, while a slow change in temperature causes only small differences. By connecting the temperature sensitive sensors into a bridge, the resistance difference can be easily detected. The temperature sensitive resistors are realized by thin film technology using platinum or nickel film on a thin glass or ceramic substrate. Because of the large surface and small volume of the resistor, its time-constant originally is very low but the time-constant could be easily increased by increasing the volume of the resistor. The present paper gives a detailed description of the analysis and the measurement of the temperature sensitive resistors with different time-constants. The technology of the films is also discussed.